2020
DOI: 10.3390/molecules25081800
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compounds from Fungi as Potential Candidates for Protease Inhibitors and Immunomodulators to Apply for Coronaviruses

Abstract: The inhibition of viral protease is an important target in antiviral drug discovery and development. To date, protease inhibitor drugs, especially HIV-1 protease inhibitors, have been available for human clinical use in the treatment of coronaviruses. However, these drugs can have adverse side effects and they can become ineffective due to eventual drug resistance. Thus, the search for natural bioactive compounds that were obtained from bio-resources that exert inhibitory capabilities against HIV-1 protease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 140 publications
(147 reference statements)
2
53
0
2
Order By: Relevance
“…To date, no studies have looked at the potential of ET to directly inhibit coronavirus replication. A recent review by Suwannarach et al [ 106 ] highlights the potential for fungal extracts, of which a major active component is ET, to demonstrate inhibitory activity on other RNA viruses such as HIV-1 and suggests a possible application for the inhibition of binding or replication of coronaviruses. Likewise, Xiao et al [ 107 ] demonstrated that pure ET was able to dose-dependently inhibit the pro-fs (human immunodeficiency virus-1 protein; HIV-1) activation of the HIV long terminal repeat region (which serves as a promoter‒enhancer for viral genome integration in host DNA) using an in vitro assay, suggesting that ET directly inhibits HIV transcription.…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…To date, no studies have looked at the potential of ET to directly inhibit coronavirus replication. A recent review by Suwannarach et al [ 106 ] highlights the potential for fungal extracts, of which a major active component is ET, to demonstrate inhibitory activity on other RNA viruses such as HIV-1 and suggests a possible application for the inhibition of binding or replication of coronaviruses. Likewise, Xiao et al [ 107 ] demonstrated that pure ET was able to dose-dependently inhibit the pro-fs (human immunodeficiency virus-1 protein; HIV-1) activation of the HIV long terminal repeat region (which serves as a promoter‒enhancer for viral genome integration in host DNA) using an in vitro assay, suggesting that ET directly inhibits HIV transcription.…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…Łoczechin et al, 2019 have reported the antiviral activity of seven different CQDs for the treatment of human coronavirus infections. In addition, Suwannarach et al., 2020 have also studied the immunomodulatory activities of fungal bioactive compounds as potential therapeutic agents against CoV. Liu, Zhou, et al, 2020 have discussed some patents disclose methodologies for treating and preventing CoV infections, which may be applicable to COVID‐19.…”
Section: Possible Vaccines For Covid‐19 Pneumoniamentioning
confidence: 99%
“…Medicinal mushrooms are an untapped resource which show potential antiviral, antiinflammatory, and immunomodulatory properties against various viruses like HSV, EBV hepatitis C virus, (HCV), human immunodeficiency virus (HIV), H1N1 strain of flu, and influenza (Ellan et al, 2019;Linnakoski et al, 2018;Muszy nska, Grzywacz-Kisielewska, Kała, & Gdula-Argasi nska, 2018). The secondary metabolites from these mushrooms such as alkaloids, non-ribosomal peptides, polyketides, and terpenoids have shown protease inhibitory activities against HIV-1 and hepatitis C virus (El-Fakharany, Haroun, Ng, & Redwan, 2010;Sato et al, 2009;Sillapachaiyaporn et al, 2019 (Lu et al, 2020;Ying et al, 2016) might also have protease inhibitory activities against the SARS-CoV-2 papain-like protease (Suwannarach et al, 2020). These mushroom extracts have bioactive polysaccharides (β-glucans) and galactomannan that are known to have immunomodulatory properties and stimulate the production of antiviral cytokines such as TNF-α, NK-cells, and macrophages (Jung et al, 2019).…”
Section: Medicinal Mushroomsmentioning
confidence: 99%